Lecciana, a New Low-Vigour Olive Cultivar Suitable for Super High Density Orchards and for Nutraceutical EVOO Production - Salvatore Camposeo; Gaetano Alessandro Vivaldi; Cinzia Montemurro; Valentina Fanelli; Marisa Cunill Canal (Agronomy, 2021)
Cultivar is the key factor for sustainability of the olive super high density planting system (SHD). ‘Lecciana’ is a new olive cultivar for oil production obtained in 1998 by a controlled cross between cv. Arbosana (♀) and cv. Leccino (♂) in a breeding program as part of an international research agreement between Agromillora Iberia S.L.U. and University of Bari. ‘Lecciana’ is the first olive cultivar of Italian descent suitable for SHD, featuring all the vegetative and productive traits required for efficient, sustainable olive growing intensification. Thanks to low vigor, early bearing (3rd year after planting), high yield efficiency (about 0.5 kg of fruits cm−2 of trunk section area) and good fruit size (3.5 g), ‘Lecciana’ could be planted with tree densities over 1,200 trees per hectare for an efficient continuous mechanical harvesting. High frost resistance, very low pistil abortion (3%), high fruit set (3%), oil content (over 19% fw) and, above all, good unsaturated fatty acids profile, polyphenols content (over 450 mg kg−1) and fruitiness median are the main distinctive characters of this new cultivar. The oils of ‘Lecciana’ fall into the category ‘nutraceutical EVOOs’ which can benefit from the specific functional health claim.